Amplexo interespecífico entre Ecnomiohyla miotympanum (Anura: Hylidae) y Rhinella marina (Anura: Bufonidae) en el estado de Hidalgo, México - Flores-Hernández, Felipe; Martínez-Coronel, Matías (Instituto de Ecología, A.C., 2014)
We report a case of interspecific amplexus between Ecnomiohyla miotympanum and Rhinella marina from Hidalgo, México. Also, we comment on the importance of this behaviour